The Influence of Relationship Marketing, Consumer Trust, and the Korean Wave on the Purchase Decision of Enhypen's Kpop Album - Maharanni Dessully; Andala Rama Putra Barusman (Komunitas Dosen Indonesia, 2025)
This study seeks to analyze the influence of relationship marketing, consumer trust, and the Korean Wave phenomenon on purchase interest and purchasing decisions of Enhypen's K-pop album in Bandar Lampung. Consumer purchasing decisions are complex processes and are influenced by a variety of factors, including relationship-based marketing aimed at building customer loyalty. In addition, consumer trust has an important role in creating purchase interest, particularly in the context of products that cannot be seen directly. The Korean Wave phenomenon, which is increasing the popularity of Korean culture, also contributes to the purchase decision of K-pop-related products. A questionnaire was circulated as part of the research methodology to 282 Enhypen fans in Bandar Lampung, with data analysis carried out using Smart-PLS technique. The outcomes shown that every variable studied had a noteworthy and constructive influence on purchase interest and purchase decisions. Relationship marketing and consumer trust have proven to play a significant part in raising purchase interest, which in turn influences purchasing decisions. The Korean Wave phenomenon acts as an additional driving factor that strengthens this relationship. This research is anticipated to offer understanding for music industry players in formulating more effective marketing strategies, as well as increasing the loyalty of K-pop fans in Indonesia